Investigation of spectral performance for single-scan contrast-enhanced breast CT using photon-counting technology: A phantom study - Ruth, Veikko; Kolditz, Daniel; Steiding, Christian; Kalender, Willi Alfred (Medical Physics, 2020)
Purpose: Contrast-enhanced imaging of the breast is frequently used in breast MRI and has recently become more common in mammography. The purpose of this study was to make single-scan contrast-enhanced imaging feasible for photon-counting breast CT (pcBCT) and to assess the spectral performance of a pcBCT scanner by evaluating iodine maps and virtual non-contrast (VNC) images. Methods: We optimized the settings of a pcBCT to maximize the signal-to-noise ratio between iodinated contrast agent and breast tissue. Therefore, an electronic energy threshold dividing the x-ray spectrum used into two energy bins was swept from 23.17 keV to 50.65 keV. Validation measurements were performed by placing syringes with contrast agent (2.5 mg/ml to 40 mg/ml) in phantoms with 7.5 cm and 12 cm in diameter. Images were acquired at different tube currents and reconstructed with 300 μm isotropic voxel size. Iodine maps and VNC images were generated using image-based material decomposition. Iodine concentrations and CT values were measured for each syringe and compared to the known concentrations and reference CT values. Results: Maximal signal-to-noise ratios were found at a threshold position of 32.59 keV. Accurate iodine quantification (average root mean square error of 0.56 mg/ml) was possible down to a concentration of 2.5 mg/ml for all tube currents investigated. The enhancement has been sufficiently removed in the VNC images, so they can be interpreted as unenhanced CT images. Only minor changes of CT values compared to a conventional CT scan were observed. Noise was increased by the decomposition by a factor of 2.62 and 4.87 (7.5 cm and 12 cm phantoms) but did not compromise the accuracy of the iodine quantification. Conclusions: Accurate iodine quantification and generation of VNC images can be achieved using contrast-enhanced pcBCT from a single CT scan in the absence of temporal or spatial misalignment. Using iodine maps and VNC images, pcBCT has the potential to reduce dose, shorten examination and reading time, and to increase cancer detection rates.
CRIS-Team Scopus Importer:2020-04-28
Keywords: breast CT; contrast enhanced; iodine quantification; photon-counting; spectral imaging